The genre structure of documentary films in the media space of Kazakhstan (Herald of Journalism, 2025)
This study explores the development of the genre structure of documentary films in Kazakhstan and the use of artistic methods. Its main objective is to identify the principles guiding the evolution of the documentary television film genre by describing its structure in Kazakhstan’s media space. A key task is to analyze the evolution of television documentary genres.The article examines the influence of audiences on genre development from a cultural anthropology perspective. It analyzes the content and structure of documentaries produced in Kazakhstan and globally.The research methods include content analysis and mathematical techniques. The study explores key aspects of genre development and identifies updated forms and stylistic features of television documentaries that meet modern standards.It reveals the interaction between documentary cinema and television, as well as the social, cultural, and ideological functions of screen art.The author provides theoretical and practical justification for developing this genre as an effective tool for shaping public consciousness and managing information flows.
Keywords: documentaries, new genres, facts, manipulations, media.